s → ∞ lim ( ζ ( s ) − 1 ) 1 / s .
Evaluate the limit above, where ζ ( s ) = t = 1 ∑ ∞ t s 1 denotes the Riemann zeta function .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
L = s → ∞ lim ( ζ ( s ) − 1 ) s 1 = s → ∞ lim ( 1 + 2 s 1 + 3 s 1 + 4 s 1 + ⋯ − 1 ) s 1 = s → ∞ lim ( 2 s 1 + 3 s 1 + 4 s 1 + ⋯ ) s 1 = s → ∞ lim 2 1 ( 1 + ( 3 2 ) s + ( 4 2 ) s + ( 5 2 ) s + ⋯ ) s 1 = 2 1 = 0 . 5
First, we express ζ ( s ) − 1 as a sum:
ζ ( s ) − 1 = n = 2 ∑ ∞ n s 1
Now, we use that, N → ∞ lim ( a ∈ A ∑ a N ) 1 / N = max A when all elements of A are positive, and thus evaluate the limit:
s → ∞ lim ( ζ ( s ) − 1 ) 1 / s = s → ∞ lim ( n = 2 ∑ ∞ n s 1 ) 1 / s = max { 2 1 , 3 1 , … } = 2 1
Problem Loading...
Note Loading...
Set Loading...
First, we can express ζ ( s ) − 1 as the sum:
ζ ( s ) − 1 = n = 2 ∑ ∞ n s 1
Then, we state that, as s goes to infinity, the following equality becomes true:
n = 2 ∑ ∞ n s 1 = ∫ 2 ∞ n s 1 d n .
(I don't really know how to formally proof this, but if you compare the graph of the step function corresponding to the sum at the left side and the graph of n s 1 , and take s closer and closer to infinity, it's quite believable =p).
Solving the integral, we find:
lim s → + ∞ ( ∫ 2 ∞ n s 1 d n . ) s 1 = lim s → + ∞ ( s − 1 ) s 1 n n s 1 , from infinity to two.
Since lim s → + ∞ s s 1 = 1 and lim s → + ∞ ( s − 1 ) s 1 = 1 , we have:
lim s → + ∞ ( s − 1 ) s 1 n n s 1 , from infinity to two = 0.5